The Role of Village Government in Overcoming Environmental Pollution Caused by Tofu Factory Waste - Andri, Muhammad; Rafie, Mohammad; Budiman, Haris; Huda, Afif Ilanul (Universitas Kuningan, 2023)
Environmental problems are inseparable from human activities, which often cause damage to nature and have far-reaching consequences for both human and animal life. This environmental damage is caused by business interests that prioritize profits over responsibility, ignoring the consequences of the production, which can pollute the surrounding environment. Therefore, this research aimed to use a socio-legal analysis and a statutory method by examining the evolution of a pungent odor and damage to the irrigation river ecosystem caused by waste from the tofu factory that operates without a business or environmental permit. The issues raised in the analysis included (1) What is the role of the village government in addressing environmental pollution caused by the tofu factory waste? (2) What efforts had the village government made regarding the environmental pollution from factory waste? In conducting the questions, the authors applied a normative juridical research method. The results showed that the village government played three primary roles in tackling the environmental pollution caused by the tofu factory waste, namely as a facilitator, a motivator, and a mediator. However, this responsibility was limited to a formal existence and guided by the provisions stipulated in Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH) and Regional Regulation 11 of 2019 concerning PPLH in Nganjuk. Permits served as juridical instruments used by government to regulate activities within society. These instruments were mandatory for all, ensuring that businesses operated within the bounds of legality. By obtaining both a business and the environmental permit, enterprises showed compliance with the law.